2011
DOI: 10.1016/j.febslet.2011.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of miR-124 induces neuroblastoma SK-N-SH cell differentiation, cell cycle arrest and apoptosis through promoting AHR

Abstract: a b s t r a c tNeuroblastoma is the most common extracranial solid tumor in children. We investigate whether miR-124, the abundant neuronal miRNA, plays a pivotal role in neuroblastoma. Knockdown of miR-124 promotes neuroblastoma SK-N-SH cell differentiation, cell cycle arrest and apoptosis. Further miR-124 is predicted to target aryl hydrocarbon receptor (AHR) which may promote neuroblastoma cell differentiation. We validate that miR-124 may suppress the expression of AHR by targeting its 3 0 -UTR. These resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 25 publications
(30 reference statements)
2
42
0
Order By: Relevance
“…Our findings are in keeping with previous data indicating that metabolic pathways are critical in ccRCC pathogenesis (17 ), and we showed that AHR signaling is altered in ccRCC. We identified and validated AHR as an overexpressed gene that is regulated by the underexpressed miR-124 in ccRCC, an interaction that already has been experimentally validated in other tumors (18 ). AHR can mediate either tumor-promoting or -inhibiting effects.…”
Section: Discussionmentioning
confidence: 84%
“…Our findings are in keeping with previous data indicating that metabolic pathways are critical in ccRCC pathogenesis (17 ), and we showed that AHR signaling is altered in ccRCC. We identified and validated AHR as an overexpressed gene that is regulated by the underexpressed miR-124 in ccRCC, an interaction that already has been experimentally validated in other tumors (18 ). AHR can mediate either tumor-promoting or -inhibiting effects.…”
Section: Discussionmentioning
confidence: 84%
“…However, miR-124 may be present in neuroblastoma but not in all types of tumours [34]. This reflects the heterogeneity and complexity of tumors; further research should be carried out to discover the mechanisms by which miR-124 differentially affects the proliferation of breast cancer and neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…By mediating inhibition of CDK6, which can regulate both cell cycle progression and differentiation [31], the up-regulation of miR-124 induced neuronal differentiation of brain tumor stem cells and inhibited proliferation of glioblastoma multiforme cell lines [29]. On the other hand, a recent research that knockdown of miR-124 promotes neuroblastoma cell differentiation, cell cycle arrest and apoptosis, indicated that miR-124 might exert diverse functions in differentiation of different cancers [32]. Thus, in agreement with these studies, our results may suggest that miR-124 play a role in the differentiation of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%